2009
DOI: 10.1002/ctpp.200910003
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Dusty Plasma on the Basis of the Langevin Dynamics

Abstract: Radial distribution functions of dusty plasma particles are calculated by the application of the Langevin dynamics to a system of particles interacting through the Yukawa potential. Proposed numerical model is first validated by the comparison of the numerical results with available experimental data. Both numerically determined and experimental radial distribution functions demonstrate a good coincidence, thus, enabling a calculation of the structural properties of dusty plasma for a wide range of parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…In experiments with a dusty plasma, pair-correlation and velocity autocorrelation functions can be accurately obtained by video recording [20,21]. As it was discussed in [16], PCF and VAF can be used to determine Γ and k S independently on additional physical information such as temperature, mass, charge or density.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with a dusty plasma, pair-correlation and velocity autocorrelation functions can be accurately obtained by video recording [20,21]. As it was discussed in [16], PCF and VAF can be used to determine Γ and k S independently on additional physical information such as temperature, mass, charge or density.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, pair correlation functions obtained using the potential (7) in the exponential approximation (3) were used. Our results were compared with results of work [23][24] (circle and triangle), EOS curves were obtained for 2D Yukawa system by Molecular Dynamic method, also with [22] (left triangle), EOS curves were obtained by Langevin Dynamics, and also with EOS (diamond), on the basis of PCF obtained by experiment [20].…”
Section: Wwwcpp-journalorgmentioning
confidence: 80%
“…To study thermodynamic properties of strongly non-ideal plasma the relation between pressure and pair correlation functions can be modified as follows [22]:…”
Section: Wwwcpp-journalorgmentioning
confidence: 99%
“…where p j is the momentum of the j th particle and ex U is the excess energy of the dust particles and background plasma particles. Following the procedure of Hamaguchi et al [3] and using equation (2) as the interaction potential , excess energy ex U may be calculated in presence of magnetic field as (7) where…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…They have found results using giant cluster expansion method in weak coupling regime and by using MD method in strongly coupled regime. Ramazanov et al [7] have found internal energy and excess pressure of Yukawa system using Langevin dynamics. Presence of magnetic field however alters the internal energy of the particulates in plasma and hence affects the points of phase transition from solid to liquid state.…”
Section: Introductionmentioning
confidence: 99%